2015
DOI: 10.3347/kjp.2015.53.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Characterization of <I>Toxoplasma gondii</I> in Pet Dogs in Central China

Abstract: The prevalence and genotype of Toxoplasma gondii infection in dogs in Henan Province, Central China was investigated. A total of 125 blood samples were collected from pet dogs during April to June 2013, and all samples were examined by indirect hemagglutination antibody test (IHA) and nested PCR. The overall T. gondii prevalence in pet dogs was 24.0% (30/125), with 20.8% (26/125) in IHA and 10.4% (13/125) in PCR, respectively. No statistical associations were found between animal gender and age and the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…No survey of the seroprevalence of T. gondii in goats in tropical China has been reported. IHAT is a simple technique for detecting T. gondii antibodies (IgG and IgM) and has been used extensively in many animals in China [ 7 , 11 , 13 , 17 ]. Therefore, the present study used IHAT to detect T. gondii antibodies in goats using a commercially marketed kit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No survey of the seroprevalence of T. gondii in goats in tropical China has been reported. IHAT is a simple technique for detecting T. gondii antibodies (IgG and IgM) and has been used extensively in many animals in China [ 7 , 11 , 13 , 17 ]. Therefore, the present study used IHAT to detect T. gondii antibodies in goats using a commercially marketed kit.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples were tested for antibodies against T. gondii by the indirect hemagglutination test (IHAT) viable kit (NY/T 573-2002, Lanzhou Veterinary Research Institute, Chinese Academy of Agricultural Sciences) according to the manufacturer’s instructions. The kit is commercially available and has been used for many years in China to detect specific antibodies to T. gondii in goats and other mammals [ 7 , 11 , 13 , 17 ]. The serum samples were identified as positive if an agglutination reaction was seen in wells with dilutions of 1:64 or higher.…”
Section: Methodsmentioning
confidence: 99%
“…The African and Asian continents were the least explored. In particular, pockets of research in Asian countries have documented patterns similar to the ones in South America [ 93 , 94 , 95 , 96 , 97 ]. Only two studies were carried out in Malaysia to genotype T. gondii strains ( Table 7 ).…”
Section: Genetic Diversity and Population Structure Of Tmentioning
confidence: 99%
“…Limited data about genotyping of T. gondii isolates from dogs in China is available. A previous study reported the genotype of T. gondii isolates from dogs in Henan province and considered it as a type I variant [ 25 ]. The present result shared the same type at the (3'+5') SAG2 loci with T. gondii isolates from dogs in Henan [ 25 ].…”
mentioning
confidence: 99%
“…A previous study reported the genotype of T. gondii isolates from dogs in Henan province and considered it as a type I variant [ 25 ]. The present result shared the same type at the (3'+5') SAG2 loci with T. gondii isolates from dogs in Henan [ 25 ]. This may suggest that T. gondii isolates from dogs in Zhanjiang city may belong to type I or a type I variant.…”
mentioning
confidence: 99%